ACADEMIC RESEARCH ENGAGEMENT IN THE ARABIAN GULF: PREDICTORS AND CROSS-COUNTRY COMPARISON - Alharbi , Noura Saleh; Mohebi , Laila Farahnaz (Top Educational Review Journal (TERJ), 2025)
Challenges remain in achieving world-class standards in teaching and research while higher education has recently developed rapidly in Arabian Gulf countries. This mixed-methods study compared research engagement among academics in the Kingdom of Saudi Arabia (KSA) and the United Arab Emirates (UAE) about demographics, institutional support, and collaborative practices. Data were collected through an online survey sent to 44 university academics. The quantitative and qualitative data were analyzed statistically and thematically. KSA universities had a balanced gender distribution while the UAE’s had a slight male majority. UAE academics reported being more motivated to conduct research than those in KSA. Regression analysis showed that forms of institutional support significantly predict research engagement in KSA but not in the UAE. Paired-sample t-tests revealed significant differences in research motivation and co-authorship with UAE academics collaborating more frequently. However, these countries had no significant differences in research engagement or institutional support. Thematic analysis indicated KSA academics were motivated more by extrinsic than intrinsic motivators. These findings suggest KSA universities need tailored policies to improve support mechanisms while UAE universities should sustain collaborative initiatives. Future research should use larger samples and longitudinal designs to explore more factors